Sociodemographic factors of non-suicidal self injury among young adults of higher instituitions in Kedah - K.c. Mani @ Subramanian, Kulanthayan; Romli, Muhammad Hibatullah; Alimuddin, Aishah Siddiqah; Ahmad, Norliza; A., Thangeswary (Community Health Society Malaysia, 2024)
Background: Non-suicidal self-injury (NSSI) is the intentional infliction of harm on one’s body without suicidal intent, affecting 8-22% of young adults globally. The study aimed to explore how sociodemographic traits such as age, sex, socioeconomic status, ethnicity, and parental education influence NSSI behavior among young adults in higher education. Methodology: A sample of 552 respondents was selected through cluster sampling, and NSSI was assessed using the Functional Assessment of Self-Mutilation (FASM). Descriptive statistics, chi-square tests, and logistic regression analyses were used to examine the data. Results: The results showed that 20.5% of males and 33.4% of females exhibited NSSI behavior, with 19-year-olds being the largest age group affected. NSSI behavior was more prevalent among Malay respondents (61.8%) and those from the lowest economic bracket (32%). Over 40% of students with secondary or diploma-level education demonstrated the highest rates of NSSI. Gender was a significant predictor, with females more likely to engage in NSSI (p = 0.042), though no significant relationships were found between NSSI and age, parental education, or family income. Conclusion: In conclusion, the study highlights significant differences in NSSI behavior by gender and educational attainment, with higher rates in females and students with lower educational backgrounds. The findings underscore the need for targeted interventions to address the specific vulnerabilities of these groups to reduce NSSI.